Self-powered triboelectric sensor for cooling fan monitoring. (1st September 2022) - Kim, Hakjeong; Hwang, Hee Jae; Kim, Wook; Hong, Seongchan; Yoon, Jongwon; Lim, Hyeongwook; Choi, Dukhyun
Abstract: Since the COVID-19 pandemic began, the use of computers, Internet of things devices, and artificial intelligence applications has dramatically increased. For the operation of these devices, it is important to effectively control the thermal management systems. Cooling fans play an important role in air circulation and thermal management for many types of industrial machines. In the past, a disassembly process has been inevitable for monitoring the operational status of cooling fans, making it necessary to develop devices or methods to monitor the operational status of cooling fans more conveniently. In this study, we propose a fan-shaped triboelectric sensor (F-TES) that can detect the operational status of a cooling fan via output signals of a triboelectric nanogenerator. We investigated the effects of rotational speed, as well as the working areas of the tribo-materials. Furthermore, we demonstrated those behaviors by using a light-emitting diode and capacitor charging. We designed an F-TES based on a commercial cooling fan without any structural changes, so that it could be directly utilized for various cooling fans. We anticipate that the results of this study can serve as a cornerstone for the maintenance and management of various commercial cooling fans.